Análise sobre gestão de documentos na Agência Distrital de Icoaraci - COSTA, Alexandre Assunção da (2021)
It analyzes the management of documents and the organization of the archive of the Icoaraci Distrital Agency, an administrative unit belonging to the Municipality of Belém, which is settled at a distance about 11.100 miles, of the capital, with a view to identifying the document flow, as well as the physical-organic composition of its documents and its generating sources; understand the functional structure, and understand their current "organization". It shows, from the analysis and the study of the documents of the archive, how to reach the proposed objective, analyze the document management and the organization of the archive, identifying possible solutions. In the archival diagnosis, it was possible to verify the real situation of the archive, when then; the analysis of this diagnosis was made, resulting in the organization proposition of the archive. Describes the methodological approach, which is an exploratory research, qualitative in nature, combining bibliographic and field research techniques for data collection. Based on this methodology, it was possible to know the mass and the document flow, the genres, the species and the types of documentaries. It concludes with the identification of misconceptions about the custody, the recovery and packaging of documents; verifies that the building where the current archive is located is outside the standards recommended by the national archival organizations. Formulate proposal of organization of the archive, in order to expedite the information storage and retrieval process; instructs the organization of the archive; and recommends the use of software developed for document management.